Editorial: Aquaculture-aided approaches for conservation and sustainable fisheries - Matthew D. Taylor; Alistair Becker; Edward V. Camp; Luis Henríquez-Antipa; Neil R. Loneragan; Kai Lorenzen (Fisheries Research, 2026)

Corrigendum to “low apex carnivore density does not release a subordinate competitor when driven by prey depletion” [Biol. Conserv. 261 (2021) 109273] - Ben Goodheart; Scott Creel; Matthew S. Becker; Milan Vinks; Paul Schuette; Kambwiri Banda; Carolyn Sanguinetti; Elias Rosenblatt; Chase Dart; Anna Kusler; Kim Young-Overton; Xia Stevens; et al. (Biological Conservation, 2026)

High‐Throughput Sequencing in Aquaculture Disease Investigations: Challenges and Opportunities for Implementation - Francisca Samsing; Phoebe Arbon; Matthew Arnold; Andrew C. Barnes; David Bass; Joy A. Becker; Jerusha Bennett; Charles Caraguel; Jeremy Carson; Vincenzo A. Costa; Thomas Dumond; Jemma Geoghegan; et al. (Reviews in Aquaculture, 2026)
The current generation of sequencing technologies can produce terabases of data with exceptional accuracy and speed, at a fraction of the cost of older methods. Despite this unprecedented power, adoption into aquaculture health management presents several challenges, including identifying where such capability may be optimally deployed. Here we synthesise discussions from a structured expert workshop held at the 2025 Aotearoa Aquatic Diseases Symposium in Dunedin, New Zealand, where experts from industry, government and academia explored the challenges and opportunities for adopting high‐throughput sequencing (HTS) to support disease investigations in aquaculture. Workshop participants identified key applications for HTS, including pathogen discovery during unexplained mortality events and source attribution in epidemics, but also noted technical, regulatory and social challenges for widespread adoption. These include the need for standardised sampling and bioinformatic workflows, data sovereignty, equitable access to the technology and uncertainty around interpreting detection of notifiable pathogens. Targeted research and coordinated regulatory frameworks will be essential to guide responsible use of HTS and determine where it adds value relative to existing approaches. Clarifying these opportunities and constraints will guide the responsible adoption of HTS into aquaculture health management to support sustainable growth for the sector.

To stock or not to stock: The paradox of releasing fish and invertebrates in estuaries - Neil R. Loneragan; Matthew D. Taylor; Zhongxin Wu; Alan Cottingham; Ryan W. Schloesser; Nathan P. Brennan; Brian Poh; Kerry Trayler; Alistair Becker; James R. Tweedley (Fisheries Research, 2026)

From rings to records: Refining the construction date of a historic cabin near Hamilton, Montana - Lauren A. Stachowiak; Grant L. Harley; Mari A. Becker; Ellen Bergan; Nick Koenig; Kai McLaughlin; Matthew R. Slater; Richard Thaxton; Karen Martel; Mark Martel (Dendrochronologia, 2026)

Prey depletion and the effect of group size on cooperative hunting in African wild dogs - Scott Creel; Ben Goodheart; Johnathan Reyes de Merkle; James Redcliffe; Henry Mwape; Stephani Matsushima; Chase Dart; Kachama Banda; Bridget Mayani; Anna Kusler; Johane Njobvu; Reuben Kabungo; et al. (Animal Behaviour, 2026)

Ecology of community reassembly: Movements and diets of megafauna during a decade of restoration in Mozambique - Matthew C. Hutchinson; Reena H. Walker; Joel O. Abraham; Justine A. Becker; Dominique D. Gonçalves; Ciara M. Nutter; Johan Pansu; Erin M. Phillips; Arjun B. Potter; Beto Soares Tenente; Marc E. Stalmans; Ryan A. Long; et al. (Ecology, 2026)
The last decade has brought a worldwide surge of interest in rewilding—the repopulation of large herbivores and carnivores—as a strategy for conserving species and reviving ecosystem functions. Rewilding initiatives, if closely monitored, can provide unique insights into the ecology of the world's largest animals at otherwise impossible spatial and temporal scales. Capitalizing on these opportunities, and developing a knowledge base to guide future restoration efforts, requires the collection and dissemination of long‐term data that document community reassembly. To date, such data are virtually nonexistent: most megafaunal restoration projects are nascent and/or have not been rigorously monitored. Since 2008, the Gorongosa Restoration Project, in Mozambique's Gorongosa National Park, has facilitated the recovery of megafauna populations that were severely depleted or extirpated during the country's civil war (1977–1992). For over a decade, we have monitored Gorongosa's large‐herbivore populations to understand how animal behavior and trophic interactions change as communities reassemble. Here, we present spatiotemporally explicit data sets on the movements and diets of large herbivores in Gorongosa between 2013 and 2025, along with annual rainfall data. This period encompassed extremes of climate (including some of the driest and wettest years on record) and the reintroduction, starting in 2018, of locally extinct apex predators and scavengers: African wild dog ( Lycaon pictus ), leopard ( Panthera pardus ), spotted hyena ( Crocuta crocuta ), and side‐striped jackal ( Lupulella adusta ). We used GPS telemetry to monitor 277 herbivores of seven species (listed below with number of individuals collared, median duration of tracking, and median number of locations per individual): Cape bushbuck ( Tragelaphus sylvaticus : 103 individuals; 280 days; 6646 fixes), nyala ( T. angasii : 37 individuals; 306 days; 6789 fixes), greater kudu ( T. strepsiceros : 80 individuals; 300 days; 17,365 fixes), common eland ( T. oryx : 10 individuals; 334 days; 15,783 fixes), waterbuck ( Kobus ellipsiprymnus : 22 individuals; 13 days; 2877 fixes), plains zebra ( Equus quagga : 7 individuals; 212 days; 1171 fixes), and African savanna elephant ( Loxodonta africana : 18 individuals; 706 days; 33,122 fixes). For 295 individuals that were immobilized during this work, we present morphological measurements (chest girth, body length, hind‐foot length, weight), reproductive status and nutritional condition (ultrasound measurements, palpation scores), and fate (mortality date and cause, if known). For diet analysis, we used DNA metabarcoding to identify and quantify the relative abundances of plant taxa in 3785 fecal samples from 27 mammal species belonging to 11 families and 7 orders. In all, we recorded 516 food‐plant taxa from at least 87 plant families and 39 orders. For Gorongosa's 15 most common large herbivores, the median sampling depth was 216 fecal samples per species (interquartile range 156–279); the overall median sampling depth was 92 samples per species (range 1–499). We include basic metadata collected in the field (e.g., date, time, GPS location, animal sex, and age) along with laboratory notes and information on plant taxonomic identification. These data are valuable not just as a window on one ecosystem's recovery from armed conflict, but also as a resource for macroecology, meta‐analysis, and synthetic studies of animal movement, diet, and the dynamics of community reassembly. The data are freely available for use and this paper should be cited whenever data are reused; see Data : Metadata : Class III.B.4 for additional details.

The influence of aquaculture translocations and escapees on the genetics of wild stocks of Lates calcarifer in Taiwan and Sri Lanka - Matthew A. Campbell; Matthew C. Hale; Nirooparaj Balachandran; Wei-Jen Chen; Joy A. Becker (Conservation Genetics, 2026)
Advances in aquaculture have significantly enhanced food production and contributed to global food security. However, the selective pressures for aquaculture are strong and divergent compared to those occurring in natural systems, and displacement of standing genetic backgrounds by aquaculture backgrounds is a conservation concern across various species. The Asian sea bass or barramundi ( Lates calcarifer ) is a widely propagated species that has undergone intensive selective breeding and extensive translocations. There are uncertain impacts, if any, on wild stocks throughout the tropical Indo-West Pacific region as a result. Using whole-genome sequencing data, we characterize the genetic background of wild-caught fish from two previously unrepresented regions – Taiwan and Sri Lanka. In Taiwan, Asian sea bass aquaculture has been ongoing for decades, largely relying on broodstock from Thailand. Aquaculture of this taxon in Sri Lanka is more recent and less understood. We also sequenced two aquaculture strains from Australia and Sri Lanka, for a total of four aquaculture strains to better characterize aquaculture strains of Asian sea bass. Our results show that Taiwanese wild-caught fish exhibit admixture with aquaculture origin, alongside introgression of Indian Ocean mitochondrial haplotypes. Conversely, Sri Lankan wild-caught fish are not admixed with the local aquaculture strain and are similar to other Indian Ocean fish. Our findings indicate that mixture of distinctive genetic backgrounds of Asian sea bass is widespread in both culture and naturally recruiting populations. This underscores the urgent need for improved hatchery management and conservation measures to safeguard the long-term sustainability and genetic integrity of wild stocks.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Responsible restocking to aid recovery of an iconic sciaenid fishery: A case study of Mulloway (Argyrosomus japonicus) - Alistair Becker; Julian M. Hughes; Ashley M. Fowler; Matthew D. Taylor (Fisheries Research, 2026)

Using acoustic telemetry to inform standardisation of catch rates from passive fishing gear: A case study using dusky flathead (Platycephalus fuscus) - Hayden T. Schilling; James A. Smith; Daniel E. Hewitt; Alistair Becker; Charles Gray; Geoffrey Liggins; Nicholas L. Payne; Dylan van der Meulen; Matthew D. Taylor (Fisheries Research, 2025)

A paired analysis of mercury among non-invasive tissues in Mexican free-tailed bats (Tadarida brasiliensis) to inform conservation monitoring - Molly C. Simonis; Kimberlee Whitmore; Kristin E. Dyer; Meagan Allira; Bret Demory; Matthew M. Chumchal; Daniel J. Becker (Ecotoxicology, 2025)
Contaminants can harm wildlife. However, measuring wildlife exposure to contaminants can be challenging due to accessibility of species and/or sampling tissue matrices needed to assess wildlife health risks. For example, in bats and other taxa that use roosts, collecting feces under colonies minimizes disturbance to species of conservation concern, but fecal contaminant concentrations may not directly correlate with tissue contaminant concentrations. Thus, there is a need for quantifying contaminant exposure relationships between sample matrices for initial risk assessments to address wildlife health and conservation needs. Our goal was to assess the relationship between fecal and fur total mercury (THg) concentrations. We collected paired feces and fur samples ( n = 48) from Mexican free-tailed bats ( Tadarida brasiliensis ) in summer 2023 in western Oklahoma at a maternity roost. At the individual level, we found no correlation between fecal and fur THg. However, at the population level, fur THg concentrations were on average 6.06-times greater than fecal THg concentrations. We conclude that although fecal THg cannot serve as a proxy of individual bat fur THg, population-level differences could be used cautiously to estimate mean fur THg concentrations from under-roost feces and motivate individual-level sampling to assess health impacts. We encourage continued research across other insectivorous bat species and sites for determining THg relationships across tissues and initial risk assessments with minimal disturbance to species of conservation concern when a contaminant point source is not yet known.

Capture Probability of Blue Swimmer Crab ( Portunus armatus ) in Baited Traps and Implications for Trap Survey Design - Alistair Becker; Daniel D. Johnson; Hugh Pederson; Matthew D. Taylor (Fisheries Management and Ecology, 2025)
Fishery independent surveys provide valuable data for fisheries assessments that predominantly rely on trends in catch per unit effort (CPUE). Many crustacean fisheries are harvested using traps, so this gear is often used for fishery independent surveys. The areal sampling unit for baited traps is normally poorly understood, so surveys can be biased if sampling areas overlap. The blue swimmer crab ( Portunus armatus ) is an important commercial and recreational species distributed around the warm temperate and tropical coast of Australia, and stock management typically relies on catch data supplemented by independent surveys. Acoustic telemetry was used to track fine‐scale movements of 37 crabs in response to deployment of baited‐traps and to estimate probability of capture relative to distance from the trap. Traps attracted crabs from an initial distance up to 70 m, with most movements towards traps after dark. Capture probability increased with decreasing initial distance from a deployed trap. Despite this, the probability of capture was

Refining submarine groundwater discharge analysis through nonlinear quantile regression of geochemical time series - Benjamin Hagedorn; Matthew W. Becker; Nyssa J. Silbiger; Brittney Maine; Ellen Justis; Danielle M. Barnas; Maya Zeff (Journal of Hydrology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Interactions between White Sharks (Carcharodon carcharias) and artificial reefs along the east-coast of Australia - Alistair Becker; Paul A. Butcher; Stephen Morris; Curtis Champion; Victor M. Peddemors; Michael B. Lowry; Matthew D. Taylor (Fisheries Research, 2024)

Wire-snare bushmeat poaching and the large African carnivore guild: Impacts, knowledge gaps, and field-based mitigation - Matthew S. Becker; Scott Creel; Mwamba Sichande; Johnathan Reyes de Merkle; Ben Goodheart; Thandiwe Mweetwa; Henry Mwape; D. Smit; A. Kusler; Kambwiri Banda; Brian Musalo; Lengwe Mwansa Bwalya; et al. (Biological Conservation, 2024)

Application of surface-layer matrix-assisted laser desorption/ionization mass spectrometry imaging to pharmaceutical-loaded poly(ester urea) films - Kayla Williams-Pavlantos; Natasha C. Brigham-Stinson; Matthew L. Becker; Chrys Wesdemiotis (Analytica Chimica Acta, 2023)

Suitability of saltmarsh creeks as release locations for stocked Mulloway (Argyrosomus japonicus) - Alistair Becker; D. Stewart Fielder; Michael B. Lowry; Matthew D. Taylor (Estuarine, Coastal and Shelf Science, 2023)

Effects of de-snaring on the demography and population dynamics of African lions - Kambwiri Banda; Scott Creel; Mwamba Sichande; Thandiwe Mweetwa; Henry Mwape; Johnathan Reyes de Merkle; Lengwe Mwansa Bwalya; Twakundine Simpamba; Rachel McRobb; Matthew S. Becker (Biological Conservation, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Implications of habitat use and movement of stocked juvenile dusky flathead ( Platycephalus fuscus ) on stock enhancement release strategies - Alistair Becker; Hugh Pederson; Michael B. Lowry; D. Stewart Fielder; Matthew D. Taylor (Fisheries Management and Ecology, 2023)
Stocking of marine fish into coastal systems to augment natural recruitment is a growing practice adopted by fisheries managers around the world. Releasing fish directly into well‐resourced nursery grounds greatly increases survival and retention of stocked individuals but requires an understanding of juvenile habitat requirements. In eastern Australia, the dusky flathead ( Platycephalus fuscus ) is a highly regarded recreationally targeted species and the focus of an emerging stock enhancement programme, although little is known of their specific nursery habitat. Using acoustic telemetry, hatchery‐reared juveniles were monitored in Lake Macquarie to quantify habitat use and dispersal. Sandy areas adjacent to edges of seagrass beds were favoured, likely as foraging habitat. Within 5 weeks after release, fish were detected 5 km from the release site, but only at locations containing seagrass beds, so stocked fish likely disperse around estuaries to regions with suitable habitat. Future releases of dusky flathead should target areas containing patchy seagrass‐sand to optimise stocking outcomes. Beyond fisheries enhancement programmes, our findings highlight the importance of structured habitat, such as seagrass beds, for juvenile fish.

Genomic analyses indicate two blue swimmer crab species in Australia, evidence for natural interspecific hybridization and genetic structure within species with implications for fisheries management and stock enhancement - HKA Premachandra; Alistair Becker; Kerry Millard; Danielle Johnston; Sankar Subramanian; Manoharan Kumar; Matthew Taylor; Wayne Knibb (Fisheries Research, 2023)

The evidence for and urgency of threats to African wild dogs from prey depletion and climate change - Scott Creel; Matthew S. Becker; Johnathan Reyes de Merkle; Ben Goodheart (Biological Conservation, 2023)

Development of a 10-m resolution maize and soybean map over China: Matching satellite-based crop classification with sample-based area estimation - Haijun Li; Xiao-Peng Song; Matthew C. Hansen; Inbal Becker-Reshef; Bernard Adusei; Jeffrey Pickering; Li Wang; Lei Wang; Zhengyang Lin; Viviana Zalles; Peter Potapov; Stephen V. Stehman; et al. (Remote Sensing of Environment, 2023)

Hot or hungry? A tipping point in the effect of prey depletion on African wild dogs - Scott Creel; Matthew S. Becker; Johnathan Reyes de Merkle; Ben Goodheart (Biological Conservation, 2023)

Mechanisms of individual variation in large herbivore diets: Roles of spatial heterogeneity and state‐dependent foraging - Reena H. Walker; Matthew C. Hutchinson; Arjun B. Potter; Justine A. Becker; Ryan A. Long; Robert M. Pringle (Ecology, 2023)
Many populations of consumers consist of relatively specialized individuals that eat only a subset of the foods consumed by the population at large. Although the ecological significance of individual‐level diet variation is recognized, such variation is difficult to document, and its underlying mechanisms are poorly understood. Optimal foraging theory provides a useful framework for predicting how individuals might select different diets, positing that animals balance the “opportunity cost” of stopping to eat an available food item against the cost of searching for something more nutritious; diet composition should be contingent on the distribution of food, and individual foragers should be more selective when they have greater energy reserves to invest in searching for high‐quality foods. We tested these predicted mechanisms of individual niche differentiation by quantifying environmental (resource heterogeneity) and organismal (nutritional condition) determinants of diet in a widespread browsing antelope (bushbuck, Tragelaphus sylvaticus ) in an African floodplain‐savanna ecosystem. We quantified individuals' realized dietary niches (taxonomic richness and composition) using DNA metabarcoding of fecal samples collected repeatedly from 15 GPS‐collared animals (range 6–14 samples per individual, median 12). Bushbuck diets were structured by spatial heterogeneity and constrained by individual condition. We observed significant individual‐level partitioning of food plants by bushbuck both within and between two adjacent habitat types (floodplain and woodland). Individuals with home ranges that were closer together and/or had similar vegetation structure (measured using LiDAR) ate more similar diets, supporting the prediction that heterogeneous resource distribution promotes individual differentiation. Individuals in good nutritional condition had significantly narrower diets (fewer plant taxa), searched their home ranges more intensively (intensity‐of‐use index), and had higher‐quality diets (percent digestible protein) than those in poor condition, supporting the prediction that animals with greater endogenous reserves have narrower realized niches because they can invest more time in searching for nutritious foods. Our results support predictions from optimal foraging theory about the energetic basis of individual‐level dietary variation and provide a potentially generalizable framework for understanding how individuals' realized niche width is governed by animal behavior and physiology in heterogeneous landscapes.

Hydroacoustic surveys reveal the distribution of mid-water fish around two artificial reef designs in temperate Australia - Alistair Becker; Michael B. Lowry; Ashley M. Fowler; Matthew D. Taylor (Fisheries Research, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Connectivity of Large-Bodied Fish with a Recovering Estuarine Tidal Marsh, Revealed Using an Imaging Sonar - Mark A. Bennett; Alistair Becker; Troy Gaston; Matthew D. Taylor (Estuaries and Coasts, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Evidence of freshened groundwater below a tropical fringing reef - Benjamin Hagedorn; Matthew W. Becker; Nyssa J. Silbiger (Hydrogeology Journal, 2020)

Temporal variability in size and growth of Atlantic herring in the Gulf of Maine - James R. Becker; Matthew D. Cieri; David A. Libby; Adam St. Gelais; Graham Sherwood; Yong Chen (Journal of Fish Biology, 2020)
Variability in life history traits and structural diversity of commercially exploited fishes in response to stress can impact their population dynamics and sustainability. Using data from a fishery dependent sampling program from 1978 to 2011, we evaluated temporal variability of size and growth of adult Atlantic herring ( Clupea harengus ) in the Gulf of Maine. We then developed and tested the hypotheses on the links of such temporal changes to population density and environmental factors and found decreases in size and growth potential. Generalized additive models found that density dependence was the main driver of such changes over sea surface temperature and salinity. Our results highlight the importance of density dependent processes in regulating growth and population size structure for Atlantic herring in the Gulf of Maine.

Steps to Develop Early Warning Systems and Future Scenarios of Storm Wave-Driven Flooding Along Coral Reef-Lined Coasts - Gundula Winter; Curt Storlazzi; Sean Vitousek; Ap van Dongeren; Robert McCall; Ron Hoeke; William Skirving; John Marra; Johan Reyns; Jerome Aucan; Matthew Widlansky; Janet Becker; et al. (Frontiers in Marine Science, 2020)

Amphibian skin fungal communities vary across host species and do not correlate with infection by a pathogenic fungus - Daniel Medina; Myra C. Hughey; Jenifer B. Walke; Matthew H. Becker; Katherine Pontarelli; Shan Sun; Brian Badgley; Lisa K. Belden (Environmental Microbiology, 2019)
Summary Amphibian population declines caused by the fungus Batrachochytrium dendrobatidis (Bd) have prompted studies on the bacterial community that resides on amphibian skin. However, studies addressing the fungal portion of these symbiont communities have lagged behind. Using ITS1 amplicon sequencing, we examined the fungal portion of the skin microbiome of temperate and tropical amphibian species currently coexisting with Bd in nature. We assessed cooccurrence patterns between bacterial and fungal OTUs using a subset of samples for which bacterial 16S rRNA gene amplicon data were also available. We determined that fungal communities were dominated by members of the phyla Ascomycota and Basidiomycota, and also by Chytridiomycota in the most aquatic amphibian species. Alpha diversity of the fungal communities differed across host species, and fungal community structure differed across species and regions. However, we did not find a correlation between fungal diversity/community structure and Bd infection, though we did identify significant correlations between Bd and specific OTUs. Moreover, positive bacterial–fungal cooccurrences suggest that positive interactions between these organisms occur in the skin microbiome. Understanding the ecology of amphibian skin fungi, and their interactions with bacteria will complement our knowledge of the factors influencing community assembly and the overall function of these symbiont communities.

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Correction to: Human–Nature Relationships and Normative Beliefs Influence Behaviors that Reduce the Spread of Aquatic Invasive Species - Carena J. van Riper; Matthew H. E. M. Browning; Douglas Becker; William Stewart; Cory D. Suski; Lara Browning; Elizabeth Golebie (Environmental Management, 2019)

Coastal groundwater discharge and the ancient inhabitants of Rapa Nui (Easter Island), Chile - Tanya Brosnan; Matthew W. Becker; Carl P. Lipo (Hydrogeology Journal, 2019)

Human-Nature Relationships and Normative Beliefs Influence Behaviors that Reduce the Spread of Aquatic Invasive Species - Carena J. van Riper; Matthew H. E. M. Browning; Douglas Becker; William Stewart; Cory D. Suski; Lara Browning; Elizabeth Golebie (Environmental Management, 2019)

Incorporating Social Diversity into Wildfire Management: Proposing “Pathways” for Fire Adaptation - Travis B Paveglio; Matthew S Carroll; Amanda M Stasiewicz; Daniel R Williams; Dennis R Becker (Forest Science, 2018)

Investigating the Functional Role of an Artificial Reef Within an Estuarine Seascape: a Case Study of Yellowfin Bream (Acanthopagrus australis) - Matthew D. Taylor; Alistair Becker; Michael B. Lowry (Estuaries and Coasts, 2018)

Boots on the ground: in defense of low-tech, inexpensive, and robust survey methods for Africa’s under-funded protected areas - Paul Schuette; Ngawo Namukonde; Matthew S. Becker; Fred G.R. Watson; Scott Creel; Clive Chifunte; Wigganson Matandiko; Paul Millhouser; Elias Rosenblatt; Carolyn Sanguinetti (Biodiversity and Conservation, 2018)

Managing the development of artificial reef systems: The need for quantitative goals - Alistair Becker; Matthew D. Taylor; Heath Folpp; Michael B. Lowry (Fish and Fisheries, 2018)
Fisheries enhancement initiatives are a potentially useful tool for managers to supplement traditional approaches. Habitat‐based enhancements often deploy artificial reefs with the aim to increase the available structure to augment local production, yet current assessment approaches make it difficult to assess whether these reefs achieve pre‐deployment goals. This makes it hard for managers to determine whether artificial reefs could improve their fishery outputs, potentially leading to missed opportunities and reduced production. We reviewed 270 research articles to determine whether existing monitoring studies identify whether artificial reefs meet their pre‐deployment goals, thereby providing some evidence of their suitability for certain fisheries. We found only 62% of these studies clearly articulated the original goals of the reef. Goals were qualitative, and most studies were conducted over insufficient time frames to allow for ecological communities to stabilize and mature. It is therefore difficult to determine the success or failure of many artificial reefs in addressing the management issues for which they were deployed. In the light of these findings, we think the setting of explicit quantitative goals (which may be biological, social or economic), and monitoring the performance of reefs against these goals, could stimulate the broader application of artificial reefs in fisheries management strategies. Such an approach has been successfully adopted in aquaculture‐based fisheries enhancement, and we explain how current evaluation methods such as harvest strategies can be easily adapted to quantitatively monitor artificial reef performance.

Direct and Indirect Interactions Between Lower Estuarine Mangrove and Saltmarsh Habitats and a Commercially Important Penaeid Shrimp - Matthew D. Taylor; Alistair Becker; Natalie A. Moltschaniwskyj; Troy F. Gaston (Estuaries and Coasts, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Dominance‐function relationships in the amphibian skin microbiome - Jenifer B. Walke; Matthew H. Becker; Myra C. Hughey; Meredith C. Swartwout; Roderick V. Jensen; Lisa K. Belden (Environmental Microbiology, 2017)
Summary Some amphibian skin bacteria inhibit growth of a fungal amphibian pathogen, Batrachochytrium dendrobatidis (Bd), but it is unclear how dominant these anti‐Bd bacteria are in skin communities. Using in vitro co‐culture challenge assays, we quantified Bd inhibition by bacterial isolates collected from the skin of four amphibian species: bullfrogs, Eastern newts, spring peepers and American toads. The 16S rRNA sequences for each isolate were matched to culture‐independent amplicon sequences from the same individuals to assess inhibitory function versus relative abundance. Dominant bacteria had higher Bd inhibition than rare bacteria in bullfrog and newt populations, in which Bd was prevalent (> 25%). Dominant and rare bacteria did not differ in Bd inhibition in spring peeper and toad populations, in which Bd was absent or at low prevalence (

Fish Movement Through an Estuary Mouth Is Related to Tidal Flow - Alistair Becker; Matthew Holland; James A. Smith; Iain M. Suthers (Estuaries and Coasts, 2016)

Organohalogen Contaminants and Vitamins in Northern Fur Seals (Callorhinus ursinus) Collected During Subsistence Hunts in Alaska - Jessica L. Reiner; Paul R. Becker; Matthew O. Gribble; Jennifer M. Lynch; Amanda J. Moors; Jennifer Ness; Danielle Peterson; Rebecca S. Pugh; Tamika Ragland; Catherine Rimmer; Jody Rhoderick; Michele M. Schantz; et al. (Archives of Environmental Contamination and Toxicology, 2016)

Cross-polarized GPR imaging of fracture flow channeling - Georgios P. Tsoflias; Christopher Perll; Matthew Baker; Matthew W. Becker (Journal of Earth Science, 2015)

Mapping global cropland and field size - Steffen Fritz; Linda See; Ian McCallum; Liangzhi You; Andriy Bun; Elena Moltchanova; Martina Duerauer; Fransizka Albrecht; Christian Schill; Christoph Perger; Petr Havlik; Aline Mosnier; et al. (Global Change Biology, 2015)
A new 1 km global IIASA ‐ IFPRI cropland percentage map for the baseline year 2005 has been developed which integrates a number of individual cropland maps at global to regional to national scales. The individual map products include existing global land cover maps such as GlobCover 2005 and MODIS v.5, regional maps such as AFRICOVER and national maps from mapping agencies and other organizations. The different products are ranked at the national level using crowdsourced data from Geo‐Wiki to create a map that reflects the likelihood of cropland. Calibration with national and subnational crop statistics was then undertaken to distribute the cropland within each country and subnational unit. The new IIASA ‐ IFPRI cropland product has been validated using very high‐resolution satellite imagery via Geo‐Wiki and has an overall accuracy of 82.4%. It has also been compared with the EarthStat cropland product and shows a lower root mean square error on an independent data set collected from Geo‐Wiki. The first ever global field size map was produced at the same resolution as the IIASA ‐ IFPRI cropland map based on interpolation of field size data collected via a Geo‐Wiki crowdsourcing campaign. A validation exercise of the global field size map revealed satisfactory agreement with control data, particularly given the relatively modest size of the field size data set used to create the map. Both are critical inputs to global agricultural monitoring in the frame of GEOGLAM and will serve the global land modelling and integrated assessment community, in particular for improving land use models that require baseline cropland information. These products are freely available for downloading from the http://cropland.geo-wiki.org website.

Phylogenetic distribution of symbiotic bacteria from Panamanian amphibians that inhibit growth of the lethal fungal pathogen Batrachochytrium dendrobatidis - Matthew H. Becker; Jenifer B. Walke; Lindsey Murrill; Douglas C. Woodhams; Laura K. Reinert; Louise A. Rollins‐Smith; Elizabeth A. Burzynski; Thomas P. Umile; Kevin P. C. Minbiole; Lisa K. Belden (Molecular Ecology, 2015)
The introduction of next‐generation sequencing has allowed for greater understanding of community composition of symbiotic microbial communities. However, determining the function of individual members of these microbial communities still largely relies on culture‐based methods. Here, we present results on the phylogenetic distribution of a defensive functional trait of cultured symbiotic bacteria associated with amphibians. Amphibians are host to a diverse community of cutaneous bacteria and some of these bacteria protect their host from the lethal fungal pathogen Batrachochytrium dendrobatidis (Bd) by secreting antifungal metabolites. We cultured over 450 bacterial isolates from the skins of Panamanian amphibian species and tested their interactions with Bd using an in vitro challenge assay. For a subset of isolates, we also completed coculture experiments and found that culturing isolates with Bd had no effect on inhibitory properties of the bacteria, but it significantly decreased metabolite secretion. In challenge assays, approximately 75% of the bacterial isolates inhibited Bd to some extent and these inhibitory isolates were widely distributed among all bacterial phyla. Although there was no clear phylogenetic signal of inhibition, three genera, Stenotrophomonas, Aeromonas and Pseudomonas, had a high proportion of inhibitory isolates (100%, 77% and 73%, respectively). Overall, our results demonstrate that antifungal properties are phylogenetically widespread in symbiotic microbial communities of Panamanian amphibians and that some functional redundancy for fungal inhibition occurs in these communities. We hope that these findings contribute to the discovery and development of probiotics for amphibians that can mitigate the threat of chytridiomycosis.

Human encroachment into protected area networks in Zambia: implications for large carnivore conservation - Fred G. R. Watson; Matthew S. Becker; James Milanzi; Moses Nyirenda (Regional Environmental Change, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

A reservoir model of tracer transport for karstic flow systems - Matthew Becker; Alberto Bellin (Hydrogeology Journal, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Mitigating amphibian chytridiomycosis with bioaugmentation: characteristics of effective probiotics and strategies for their selection and use - Molly C. Bletz; Andrew H. Loudon; Matthew H. Becker; Sara C. Bell; Douglas C. Woodhams; Kevin P. C. Minbiole; Reid N. Harris (Ecology Letters, 2013)
Probiotic therapy through bioaugmentation is a feasible disease mitigation strategy based on growing evidence that microbes contribute to host defences of plants and animals. Amphibians are currently threatened by the rapid global spread of the pathogen, Batrachochytrium dendrobatidis (Bd), which causes the disease chytridiomycosis. Bioaugmentation of locally occurring protective bacteria on amphibians has mitigated this disease effectively in laboratory trials and one recent field trial. Areas still naïve to Bd provide an opportunity for conservationists to proactively implement probiotic strategies to prevent further amphibian declines. In areas where Bd is endemic, bioaugmentation can facilitate repatriation of susceptible amphibians currently maintained in assurance colonies. Here, we synthesise the current research in amphibian microbial ecology and bioaugmentation to identify characteristics of effective probiotics in relation to their interactions with Bd , their host, other resident microbes and the environment. To target at‐risk species and amphibian communities, we develop sampling strategies and filtering protocols that result in probiotics that inhibit Bd under ecologically relevant conditions and persist on susceptible amphibians. This filtering tool can be used proactively to guide amphibian disease mitigation and can be extended to other taxa threatened by emerging infectious diseases.

The size of savannah Africa: a lion’s (Panthera leo) view - Jason Riggio; Andrew Jacobson; Luke Dollar; Hans Bauer; Matthew Becker; Amy Dickman; Paul Funston; Rosemary Groom; Philipp Henschel; Hans de Iongh; Laly Lichtenfeld; Stuart Pimm (Biodiversity and Conservation, 2013)

Reconstruction of past methane availability in an Arctic Alaska wetland indicates climate influenced methane release during the past ~12,000 years - Matthew J. Wooller; John W. Pohlman; Benjamin V. Gaglioti; Peter Langdon; Miriam Jones; Katey M. Walter Anthony; Kevin W. Becker; Kai-Uwe Hinrichs; Marcus Elvert (Journal of Paleolimnology, 2012)

Anchoring the dog to its relatives reveals new evolutionary breakpoints across 11 species of the Canidae and provides new clues for the role of B chromosomes - Shannon E. Duke Becker; Rachael Thomas; Vladimir A. Trifonov; Robert K. Wayne; Alexander S. Graphodatsky; Matthew Breen (Chromosome Research, 2011)

Development of a numerical groundwater flow model using SRTM elevations - Kyle C. Fredrick; Matthew W. Becker; L. Shawn Matott; Ashish Daw; Karl Bandilla; Douglas M. Flewelling (Hydrogeology Journal, 2007)

B.B.S Singhal and R.P. Gupta: Applied Hydrogeology of Fractured Rocks - Matthew Becker (Hydrogeology Journal, 2002)

Use of deuterated water as a conservative artificial groundwater tracer - Matthew W. Becker; Tyler B. Coplen (Hydrogeology Journal, 2001)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)